PERTIMBANGAN HUBUNGAN SUAMI ISTRI DALAM PUTUSAN HAKIM CERAI GUGAT PERSPEKTIF MASLAHAH MURSALAH - Afifah. HS, Nur; muljan, Muljan; Arnita Sari, Dewi; Febriany, A. Very (Jurnal AL-SYAKHSHIYYAH Jurnal Hukum Keluarga Islam dan Kemanusiaan, 2025)
The phenomenon of increasing divorce cases in Indonesia shows that women are becoming more legally aware, but at the same time they still face structural barriers in the religious court process. One example of this can be seen in Decision Number 10/Pdt.G/2022/PA.Wtp at the Watampone Religious Court, where the judge dismissed the divorce petition because the parties were still in a marital relationship after the petition was filed. This study aims to analyze the basis of the judge's considerations in this case from the perspective of maslahah mursalah. The results of the study show that the judge applied the principle of dar'u al-mafasid muqaddam 'alā jalb al-maşālih by rejecting the lawsuit (Niet Ontvankelijk Verklaard). The aim was to preserve hifz al-nasl (lineage) and prevent harm in the form of uncertainty regarding the legal status of children, as well as to preserve the integrity of the household. Normatively, this decision upholds the maqasid syariah (objectives of Sharia law). However, in practice, the interpretation of maslahah mursalah must be refined by increasing gender sensitivity and considering al-maslahah al-fardiyyah (individual interests) to achieve substantive justice